La gouvernance de la Fédération Française de Tennis entre 1970 et 2020 : entre autonomie et dépendances dans la relation à la sphère publique - Bayle, E. (Movement & Sport Sciences - Science & Motricité, 2021)
The French Tennis Federation (FFT) is one of the major national sports federations and the second in France behind that of football in terms of number of licensees, economic resources and professionalization. In a model of organization of French sport strongly supported and controlled by the State and more broadly by the public sphere, the FFT delegating a public service mission made at first sight is an exception. It has built its business and organizational model around a very lucrative event: Roland Garros (RG). At first glance, it seems that it founded an autonomous development - failing to be independent - via a singular private business model allowing it to quickly depend weakly on the State. However, we show that the support of the public sphere also created in parallel a system of multiple dependencies that could either promote or limit the development of the FFT and its clubs. This observation is reflected in two major phases of its development: the "Chatrier revolution" (1968-1992) and the "period of maturity" (1993-2020). These relationships have led to a governance of compromise to anchor a development strategy aimed at optimizing and legitimizing public support. They have also been geared to the benefit of existing leaders. These relationships could take several forms: political networks, direct and indirect support at different levels of the federal pyramid, influence on the organizational governance framework. It will therefore be discussed what the strategies of empowerment but also of acceptance and management of dependencies in relation to the public sphere reveal: ambiguities and political games around the image and passions and the ecosystem around French and RG tennis whose leaders played to keep themselves in power; paradoxes between managing a public service mission and hyper; and difficulties to transform and evolve the governance model and the ability to self-reform given the dependencies created.